Maximizing Learning Through Cohesion: Contributions From a Nonlinear Approach - Dimas, Isabel Dórdio (2020)
This study explores the relationship between team cohesion and team learning by adopting a nonlinear approach. A quantitative study with a sample composed of 82 organizational teams was conducted. Radial Basis Function (RBF) interpolation models were used and results showed that the best predicting ability was obtained by the Thin Plate RBF model, which revealed that an increase in both dimensions of cohesion leads to an increase in team learning up to a certain threshold. Moreover, our results showed that the maximum value of team learning is obtained at higher values of task cohesion and moderate values of social cohesion.